Myocardial Regeneration via Progenitor Cell-Derived Exosomes - Janita A. Maring; Christien M. Beez; Volkmar Falk; Martina Seifert; Christof Stamm (Stem Cells International)
In the past 20 years, a variety of cell products has been evaluated in terms of their capacity to treat patients with acute myocardial infarction and chronic heart failure. Despite initial enthusiasm, therapeutic efficacy has overall been disappointing, and clinical application is costly and complex. Recently, a subset of small extracellular vesicles (EVs), commonly referred to as “exosomes,” was shown to confer cardioprotective and regenerative signals at a magnitude similar to that of their donor cells. The conceptual advantage is that they may be produced in industrial quantities and stored at the point-of-care for off-the-shelf application, ideally without eliciting a relevant recipient immune response or other adverse effects associated with viable cells. The body of evidence on beneficial exosome-mediated effects in animal models of heart diseases is rapidly growing. However, there is significant heterogeneity in terms of exosome source cells, isolation process, therapeutic dosage, and delivery mode. This review summarizes the current state of research on exosomes as experimental therapy of heart diseases and seeks to identify roadblocks that need to be overcome prior to clinical application.